Praksis Islam Dalam Meretas Keadaban Indonesia Multikultural - Achmad Fauzi (Millah: Journal of Religious Studies, 2012)
This paper discusses the historicity of Islam and state relations, diversity of views among Muslim tradisionalists and modernist on the relation of Islam and the state, and ideal configuration of the relation of Islam and the state. By mapping analysis of contemporary-crucial cases, it is found the need to reposition of the state as a facilitator of religious life by taking part religion in all aspects of civic life.